INVESTIGATION OF PROPERTIES OF CONCRETE WITH SEASHELLS AS A COARSE AGGREGATE REPLACEMENT IN CONCRETE - H G, Nahushananda Chakravarthy; Mutusva, Tatenda (MATTER: International Journal of Science and Technology, 2015)
This paper represents the experimental results of a concrete using seashell as a partial replacement. The present work is to investigate the effects of seashells in concrete production to produce high strength concrete. The compressive strength, flexural strength and split tensile strength tests were carried out with different proportioned sea shells at different curing days, as well as finding the optimum percentages of sea shell replacements to give targeted strengths. The concrete samples were prepared by adding seashells about 0%, 10%, 20%, 30% and 40% as a partial replacement to coarse aggregate. All these samples were cured for 7 days, 14 days and 28 days before the compressive, split tensile and flexural test were carried out. A total of 135 specimens were casted and tested for five mixtures in their proportions so as to determine the mechanical properties of the concrete. It should be noted that no additives were added to the mix except sea shell as a partial replacement coarse aggregate. A total of 45 cubes were casted for compressive strength test with dimensions of (150mm x150mm x150mm) and 45 prisms were casted for flexural strength test with dimensions of (100mm x100mm x300mm) and remaining 45 cylinders casted for split tensile strength test with dimensions of (100mm x200). After these tests were carried out, the results were used to compare with those of the control experiment. The results showed a decrease in density due to increase in seashell content and a high strength value obtained for 20% replacement. It was noted that implementing seashells in the concrete mix can be used to produce a lightweight concrete with high strength.